Diversity and morphology of abdominal glands in workers of the ant genus myopias (formicidae, ponerinae) - Hashim, Rosli; Ito, F.; Billen, J.; Stroobants, Z.; Wenseleers, T. (2013)
Histological examination of serial sections through the abdomen of workers of three species of Myopias ants revealed the presence of several exocrine glands. These include the common venom and Dufour glands as well as the pygidial gland, but also more specific sternal glands and glands associated with the sting base and the gonostyli. Two of these glands have not been reported previously among ants: one is the paired oblong plate gland, that occurs next to the oblong plate and may have a pheromonal function. The other novel gland is the paired sting shaft gland, that occurs at the dorsal side in the proximal region of the sting shaft. A remarkable characteristic of these Myopias ants is that all glands of class-3 show ducts with gradually widening internal diameter. Myopias emeryi shows a clearly more simple variety of abdominal glands than Myopias maligna and M. sp.1. (C) 2013 Elsevier Ltd. All rights reserved.